Effectiveness of The “Healthy Teeth, Bright Smile” Program Using The CIPP Model in Forming Children's Dental Health Habits KB Bina Rabbani - Juriah, Icah; Arizka, Pilma Sindy (Jurnal Tematik, 2025)
This research aims to evaluate the effectiveness of the "Gigiku Sehat, Senyumku Cemerlang" program using the CIPP model in forming dental health habits in early childhood at KB Bina Rabbani, Medan. The method used is qualitative descriptive with the CIPP evaluation model (Context, Input, Process, Product). The subjects were 20 Group B children consisting of 12 girls and 8 boys. Data collection techniques included in-depth interviews, participatory observation, documentation, knowledge tests, skills checklists, and clinical examinations. The results showed the program was highly effective in increasing knowledge (75-95%), skills (80-95%), positive attitudes (70-92%), habit formation (70-87%), and improving dental health conditions (80-96%). From the Context aspect, the program is highly relevant to children's needs with dental caries prevalence reaching 81.1%. From the Input aspect, resource readiness reached 95% including professional medical personnel, age-appropriate educational materials, and adequate facilities. From the Process aspect, program implementation ran smoothly with high child involvement (85-92%) despite minor obstacles. From the Product aspect, the program successfully achieved its objectives holistically. Thus, it can be concluded that the "Gigiku Sehat, Senyumku Cemerlang" program is effective and strategic in building dental health habits in early childhood through comprehensive synergy between schools, medical personnel, and families.
Keywords: Dental Health; CIPP Evaluation; Healthy Habits; Early Childhood Education; Dental Caries